Perlindungan Hukum Kreditur Pemegang Hak Tanggungan dalam Kasus Objek Jaminan dari Hasil Tindak Pidana Korupsi (Studi Putusan Pengadilan Negeri Bitung Nomor 70/Pdt.Bth/2015/PN Bit) - M. Alfathan; sutiarnoto; Suhaidi (CV Rewang Rencang, 2025)
The legal protection of creditors holding mortgage rights in cases where collateral objects originate from corruption crimes is analyzed through a case study of Bitung District Court Decision Number 70/PDT.BTH/2015/PN.BIT. The findings indicate a hierarchical conflict between criminal law and civil law. Criminal verdicts do not automatically nullify the property rights of good-faith third parties. Mortgage Right Certificates possess executorial power equivalent to court decisions and grant preferential rights to creditors. The court ruled that the seizure was unlawful because the mortgage right had been previously encumbered. Special regulations are needed to protect third-party rights and establish validation mechanisms before seizing collateral objects.